Late effects of heavy-ion space radiation on splenocyte subpopulations and NK cytotoxic function - Leung, Calvin N.; Howell, Donna M.; De Toledo, Sonia M.; Azzam, Edouard I.; Howell, Roger W. (Frontiers in Astronomy and Space Sciences, 2022)
With current goals of increased space exploration and travel to Mars, there has been great interest in understanding the long-term effects of high atomic number, high energy (HZE) ion exposure on various organ systems and the immune system. Little is known about late effects on the immune system after high-LET exposure. Therefore, our objective was to determine how natural killer (NK) cell populations were affected in geriatric mice that were exposed to HZE particles during middle-age, thereby representing elderly retired astronauts that undertook deep space missions. Methods: 10 month old male CBA/CaJ mice were whole-body irradiated: sham (control); 150-cGy gamma-rays (delivered in 1 fraction); 40-cGy 1-GeV/nu 28Si14+ ions (delivered in 3 fractions); 40-cGy 1-GeV/nu 16O8+ ions (1 fraction); and 40-cGy 1-GeV/nu 16O8+ ions (3 fractions). The mice were sacrificed 1-1.5 yr post-exposure, and the spleens harvested. Splenocyte effector (E) cells were harvested and added to 51Cr-labeled Yac-1 target (T) cells in E:T ratios of 12:1, 25:1, 50:1, and 100:1. NK cytotoxicity was measured with 51Cr release. In addition, 2 million splenocytes were aliquoted and stained with a seven-antibody cocktail, and flow cytometry was used to determine the percentage of NK, B lymphocytes, and T lymphocytes in the splenocyte population. Results: Mice exposed to either a single fraction of 150-cGy gamma rays or 40-cGy 16O8+ ions in 3 fractions were found to have significant decreases in NK cytotoxicity of approximately 30% and 25%, respectively. No significant differences were observed in NK cytotoxicity for 40-cGy 16O8+ ions delivered in 1 fraction, or 40-cGy 28Si14+ ions delivered in 3 fractions. No significant differences were observed in the percentage of spleen cells that were NK (%NK) amongst the groups. Conclusion: Fractionated HZE ion exposure has the potential to affect the innate arm of the immune system long after exposure, leading to decreases in NK cell function. Therefore, protective countermeasures may need to be considered to decrease the risk of reduced long-term immune function in elderly retired astronauts that undertook deep space missions.